Education and social mobility - Helena Holmlund; Martin Nybom (Institute for Evaluation of Labour Market and Education Policy (IFAU), 2023)
Education policy holds the promise of breaking the strong ties between family background and socio-economic position by providing publicly accessible education for children of all backgrounds. However, the education system may also perpetuate social inequalities if well-off families are able to protect their children from downward mobility by e.g., moving to neighbourhoods with high-quality schools, and by providing networks that offer opportunities to succeed. A growing number of studies however show that educational interventions can have long-lasting effects on students' outcomes, in particular for disadvantaged students, and that they can be cost-effective. For example, reducing class size, increasing general education spending, tutoring and improved teacher quality are policy levers that are shown to be successful in this regard. Shifting from selective to comprehensive school systems is also a policy that enhances equality of opportunity. While the evidence on credit constraints and their role for access to higher education is evolving but still mostly US focused and largely inconclusive, it is a key domain for shaping social mobility given the life-changing impacts that a university degree can have.
Keywords: I3; I24; J24; 330; Equality of opportunity; social mobility; intergenerational mobility; education policy; economics of education; effect evaluation